(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Present study includes the description of four species of the genus Marpissa C. L. Koch, 1846 collected from different areas of Bangladesh of which one species is described as new to science and other three species are new records for the area of present study. The recorded species are-Marpissa dhakuriensis Tikader, M. ludhianensis Tikader, M. mandali Tikader and M. longinoda n. sp. An illustrated description and distribution together with a key to the species are provided herewith. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 73-80